Chlorhexidine added to different adhesive systems - Assessment of antibacterial activity and bond strength (Research, Society and Development, 2022)
This study aimed to assess the effects of adding chlorhexidine (CHX) to different adhesive systems on antibacterial activity and bond strength after 24 hours and 30 days under in vitro conditions. A total of 210 bovine incisor crowns and divided into three groups, based on the adhesive system: Single Bond Plus (SB), Clearfil SE Bond (CL), and AdheSE Primer and Bond (AD). All groups were subdivided by CHX concentration (n=7): no CHX, CHX applied before the adhesive (CPA), and the adhesive incorporated with 0.5% CHX, 1.0% CHX, and 2.0% CHX. The micro shear test was conducted on one-half of the specimens after 24 hours, and on the other half after 30 days. Antibacterial activity was evaluated using the agar diffusion test with Streptococcus mutans. The bond strength variable was assessed using the factorial analysis of variance for repeated measurements, whereas the variable of the bacterial halo size was subjected to the Kruskal–Wallis nonparametric test. The significance level was 5% for both tests. The qualitative variable of fracture pattern was assessed by descriptive statistical analysis. Thus, CHX concentration of 2% (10.80 ±2.83) and CPA (9.95 ±1.47) (p >0.05) helped to increase the bond strength values for most adhesive systems, whereas CL had the highest bond strength values. The CL adhesive system also presented the best results in the antibacterial test with S.mutans.